Kegiatan Program Pengabdian Masyarakat Kelompok 073 Berbasis Masjid Di Kelurahan Jenggalu - Lena Hariana; Michael Pratama; Fakhrurrozi Hanafiah; Sinta Nurlita; Regita Dwi Silvana; Mutiara Ardila; Median Susanti; Elsy Riana Sari; Ahmad Khusin Huda (Pakis Journal Institute, 2024)
This community service program, conducted by Group 073 of UINFAS Bengkulu, aimed to address several key issues in Kelurahan Jenggalu, including mosque cleanliness, religious education, and disaster relief. The primary objectives were to enhance mosque facilities, promote religious learning through regular Quranic studies, and provide support to flood victims. The program employed a participatory approach involving activities such as mosque cleaning, Quranic education sessions, a Muharram competition, health exercises, and assistance for flood-affected families. Data was collected through direct observation, questionnaires, and interviews with participants and mosque officials. The results indicated a significant improvement in mosque cleanliness, increased community engagement in religious activities, and positive feedback on disaster relief efforts. The activities successfully fostered greater community involvement and addressed the pressing needs of the local population, demonstrating the effectiveness of mosque-based community programs in enhancing social welfare.